Upaya Pencegahan Stunting pada Anak dengan Membuat Kebun Stunting di Desa Batu Gajah - Bunga Chintia Utami; Annisa Aulia Insani; Atilla Ramadhanilla; David Charlos Bakara; Elviera Putri; Islah Oktaviani; Nadya Zahrah; Nopti Eliansi Lubis; Nur Azisah; Raihan Putra Hidayat; Wahyu Kurniawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Stunting is a disorder of growth and development in children caused by chronic malnutrition and recurrent infections, characterized by height below normal. Batu Gajah Village is one of the villages in Tapung district, Riau province where KUKERTA UNRI 2023 students perform community service by promoting high-end employment programs, specifically reducing underdevelopment. This work program is implemented as a primary preventive measure so that the rate of stunting in Indonesia will decrease, because stunting is currently a serious problem facing the government. The method used by Kukerta students to prevent stunting is to perform community service by going directly to the field and interacting directly with the community through activities in the work program that takes place once a week. Riau Kukerta University Student Activity Results 2023 Results is a community service in Batu Gajah Village, Tapung District, Kampar Regency, with the main objective of developing and providing education on condition prevention efforts stunting malnutrition by providing solutions in the form of consumable foods to prevent stunting, specifically establishing a stunting prevention garden, socializing stunting, and planting 4 avocado trees. At Batu Gajah Village, there is great hope that through all this, one can feel the benefits, increase the education and understanding of the Batu Gajah Village community on the prevention of stunting. This is a form of support for the government program to reduce the rate of stunting in Indonesia and help improve the country's economy through activities carried out by students of Kukerta Riau University 2023 in Batu Gajah village.